THE EFFECT OF FRAUD DIAMOND IN DETECTING FRAUD - Julia, Julia; Novel, Puput; Zaenab, Waode (LPPM STIE Muhammadiah Bandung, 2021)
This study aims to determine the effect of diamond fraud in detecting fraud. This study used qualitative research methods. The type of data source in this study is secondary data with library research techniques. Research is developed first to explain the development of the Diamond Fraud and its implementation. Next, the researcher will analyze the Fraud Diamond Theory by contextualizing it with financial statements. The presentation of writing is done systematically and correlatively. Based on the results of the study, it can be concluded that based on the theory of silent fraud, people who will commit fraud must have the ability to recognize open doors as opportunities and take advantage of them. Meanwhile, various factors can influence a person's decision to commit fraud, namely incentives, opportunity, capability and rationalization. Discussions related to the fraud diamond theory can add value to the discipline of fraud detection/prevention.